Formation of an evaluation information model in the system of land cadastre - Kuryltsiv, R.; Myronov, O. (Land Management, Cadastre and Land Monitoring, 2023)
The article examines the feasibility of developing an evaluation information model for use in the system of land administration in Ukraine. The Land Administration Domain Model (LADM) standard, which is intended to standardize cadastre models of different countries of the world, is considered. The conceptual principles of the evaluation information model and the conformity of this model to the Land Administration Domain Model (LADM) are revealed. Features of the basic evaluation information model structure are presented, including identification of information needs, and establishment of relationships between classes of objects and their filling. This approach automates the process of data collection and analysis, as well as reduces the number of errors during evaluation. The article examines the implementation of the evaluation information model based on LADM in Ukraine, which will require a comprehensive study of the legal and regulatory framework related to the system of land administration in Ukraine. For the successful implementation of the evaluation information system in Ukraine, the authors propose to define types of ownership, which will include the model, spatial-territorial distribution, and types of tax payments, which will be administered in the system. Thus, a well-developed and implemented model of land administration can provide effective management of land resources, an increase of investments, and generation of incomes. Keywords: valuation valuation model, land administration system, land administration domain model (LADM), real estate taxation